Glucagon-like peptide-1 receptor agonist use is associated with reduced risk of out-of-hospital cardiac arrest in women with type 2 diabetes: A nationwide nested case-control study - Talip E. Eroglu; Ruben Coronel; Fredrik Folke; Gunnar Gislason (Resuscitation Plus)
Objective: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) improve cardiovascular outcomes in patients with type 2 diabetes, but few studies have studied the risk of out-of-hospital cardiac arrest (OHCA). We investigated whether GLP-1 RA use reduce OHCA risk in type 2 diabetes when compared to dipeptidyl peptidase-4 inhibitor (DPP-4i) use. Methods: We identified all patients having a redeemed prescription of a glucose-lowering drug between 1995 and 2019 and excluded patients with a first-time redeemed prescription consisting of insulin. Within this cohort, we nested a case-control population comprising all OHCA-cases from presumed cardiac causes between 2013 and 2019. OHCA-cases were matched 1:5 to non-OHCA controls of the same sex and age on the date of OHCA. The odds ratios (ORs) and corresponding 95% confidence intervals (95%-CIs) of OHCA were reported comparing GLP-1 RAs versus DPP-4is. Results: We identified 3,618 OHCA-cases from presumed cardiac causes and matched them to 18,090 non-OHCA controls. GLP-1 RAs were used by 269 (7.44%) cases and 1297 (7.17%) controls, and conferred no increase in the overall odds of OHCA compared with DPP-4i use (OR:0.89, 95%-CI 0.74–1.07). However, stratification according to sex revealed that OHCA risk was significantly reduced in women (OR:0.59, 95%-CI 0.40–0.86) but not in men (OR:1.01, 95%-CI 0.82–1.26, P-value interaction:0.0093). The OR of OHCA did not vary significantly when stratifying for age, duration of diabetes, chronic kidney disease, or presence of cardiovascular disease. Conclusion: Our findings indicate that GLP-1 RA use is not associated with a reduced risk of OHCA in Danish individuals with type 2 diabetes when compared to DPP-4is.